Filicineae, Gymnospermae and Other Monocots Excluding Cyperaceae : Ferns, Conifers, and Other Monocots Excluding Sedges - Mohlenbrock, Robert H., 1931- (Book collections on Project MUSE., 2006)
"Aquatic and standing water plants of the central Midwest from orchids to cattails. This convenient reference volume includes descriptions, nomenclature, ecological information, and identification keys to plants in all of the monocot families except sedges - which are covered in the first volume in the series - that are found in Kentucky (except for the Cumberland region), Ohio, Indiana, Illinois, Iowa, Missouri, Kansas, and Nebraska. Monocots covered in this volume include ferns, conifers, grasses, rushes, orchids, duckweeds, irises, sweet flags, arrowheads, aroids, flowering rushes, pipeworts, frog-bits, arrowgrasses, naiads, pickerelweeds, pondweeds, bur reeds, cattails, and yellow-eyed grasses. Robert H. Mohlenbrock includes three types of plants: submergents, those that spend their entire lives with their vegetative parts either completely submerged or at least floating on the water's surface; emergents, which are typically rooted under-water with their vegetative parts standing out of water; and a third category of plants that live most of their lives out of water, but which may live in water at least three months a year. With taxa arranged alphabetically, the volume is well organized and easy to use. In addition, basic synonymy, description, distribution, comments, and line drawings show the habits and distinguishing features for each plant. Habitat and nomenclatural notes are also listed, as are the official wetland designations given by the U.S. Fish and Wildlife Service."--NHBS Environment Bookstore